2020
DOI: 10.3390/ijerph17176245
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Feasibility of HPV Self-Sampling as an Alternative Primary Cervical Cancer Screening in Under-Screened Population Groups: A Cross-Sectional Study

Abstract: Background: Cervical cancer is one of the most common cancers in women and about 90% of cervical cancer can be reduced by regular screening. The Pap smear has been well in place as a primary cervical screening method since 1950s; however, coverage is still not optimal. This study explored the feasibility of HPV self-sampling in two under-screened population groups in Hong Kong (HK): never screened and not regularly screened females, to estimate the uptake rate and preference rate in the future. Materials and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…Nonetheless, the acceptability of self-sampling is highly variable among different settings, social backgrounds and age groups [ 20 , 21 ]. In our study, women in the older age group were significantly less confident in performing self-sampling compared to the younger age group, which contrasts with another local study where the confidence was similar among younger and older age groups [ 17 ]. One potential reason is that the women in the older age group may have experienced conventional smears previously and feel more confident with clinician sampling.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the acceptability of self-sampling is highly variable among different settings, social backgrounds and age groups [ 20 , 21 ]. In our study, women in the older age group were significantly less confident in performing self-sampling compared to the younger age group, which contrasts with another local study where the confidence was similar among younger and older age groups [ 17 ]. One potential reason is that the women in the older age group may have experienced conventional smears previously and feel more confident with clinician sampling.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that 89.2% of the under-screened women in our study were willing to have self-sampling again, as it can be asserted that obtaining a sample in the privacy of one’s own home may eliminate some of the factors that currently deter women from attending cervical screenings. Self-sampling is recognised as an easy, convenient collection method, with most participants being confident with the procedure and having a positive experience and minor discomfort, as found in several studies [ 17 , 18 , 19 ] including ours. Nonetheless, the acceptability of self-sampling is highly variable among different settings, social backgrounds and age groups [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 53%
“…As HPV self-sampling test necessitates women performing the test themselves, it is thus critical that they feel confident in doing so. Participants in previous studies who took the HPV test stated that it was a userfriendly and straightforward test; thus, they felt confident and preferred it to cytology testing (Murchland et al, 2019;Wong et al, 2020). However, in this review, three included studies mentioned that Muslim women felt less confident in doing the test (Lofters et al, 2017;Abdullah et al, 2018;Afzal et al, 2020).…”
Section: Negative Factorsmentioning
confidence: 88%
“…Self-sampling as an alternative method of screening can overcome barriers, such as access to the health facility and fear associated with pelvic examination, opening new possibilities of reaching underscreened women (112). Acceptability of selfsampling has been reported across cultures and resource-settings (113)(114)(115)(116)(117). HPV self-sampling has the potential to make HPV testing more affordable and cost-effective by increasing screening coverage (118).…”
Section: Priority Research Questions For Primary Prevention Strategiesmentioning
confidence: 99%